THE CHANGES OF STUDENTS’ MATHEMATICAL HABIT OF MIND IN ONLINE LEARNING - Santy Setiawati; Widyastuti Widyastuti; Mella Triana; Bambang Sri Anggoro; Muhammad Ferdiansyah; Suherman Suherman; Widia Ayu Juhara (Jurnal Pengajaran MIPA, 2021)
The Covid-19 pandemic has forced changes in learning from preliminary education to higher education. The preferences of blended learning strategies at the beginning of the pandemic period and online learning for one semester had an impact on various aspects of student competences. For this reason, quantitative research was conducted which aims to describe changes in mathematical habit of mind as one of the competencies in students' thinking abilities. The population of this research was all students of mathematics education Lampung University in academic year 2020/2021. 73 students had been chosen randomly as the research sample. The research instruments were the questionnaire of mathematical habit of mind, questionnaire response of online learning implementation and interview guidelines. Based on data analysis, it can be concluded that there was no significant improvement on students’ mathematical habit of mind, after one semester of implementation fully online learning. To provide positive changes to MHoM students in online learning settings, complete and complete learning resources and synchronous communication patterns with adaptive and spontaneous feedback are needed.